2006
DOI: 10.1001/archsurg.141.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Esophageal Body Motility Disorders Underlie Aggravation of GERD Symptoms in Morbidly Obese Patients Following Adjustable Gastric Banding

Abstract: Preexisting gastroesophageal reflux disease (GERD) and esophageal motility disorders may affect the outcome of laparoscopic adjustable gastric banding (AGB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 26 publications
3
80
0
Order By: Relevance
“…Esophageal dilation found in barium studies reported in literature show an incidence ranging from 0.5% to 77.9% [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] (Table 4). A few reports mention esophageal dilation as one of the reasons for reoperating after LASGB (1.8-4.1% of the reoperations) [10,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esophageal dilation found in barium studies reported in literature show an incidence ranging from 0.5% to 77.9% [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] (Table 4). A few reports mention esophageal dilation as one of the reasons for reoperating after LASGB (1.8-4.1% of the reoperations) [10,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Klaus et al [17] reported that dilation was related to poor esophageal motility. However reports about the long-term effects of esophageal dilation on esophageal motility are lacking, and the role of altered motility in the development of esophageal dilation also is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That may be related to the complex physiological modifications induced by bariatric surgery. Several studies have suggested that esophageal-gastric peristalsis is altered after gastric banding [5][6][7]. Moreover, lower esophageal sphincter relaxation impairment is also reported [6,8].…”
Section: Middle Paragraphsmentioning
confidence: 99%
“…If the preoperative esophageal manometry shows a weak esophageal body motility, the patient is condemned to have esophageal stasis at the mid follow-up period, resulting in GERD-like symptoms with esophageal dilation [2,3]. This problem more often occurs if a technique without gastric pouch formation is used [4,5].…”
mentioning
confidence: 99%